2019
DOI: 10.3389/fbioe.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Composite Scaffold With Phosphoserine Signaling for Bone Tissue Engineering Application

Abstract: In guided bone tissue engineering, successful ingrowth of MSCs depends primarily on the nature of the scaffold. It is well-known that only seconds after implantation, biomaterials are coated by a layer of adsorbed proteins/peptides which modulates the subsequent cell/scaffold interactions, especially at early times after implantation. In this work, nanohydroxyapatite and collagen based composite materials (Coll/nanoHA) were modified with phosphorylated amino acid (O-phospho-L-serine–OPS) to mimic bone tissue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…These scaffolds under osteoinduction medium were characterized by DNA concentration, ALP activity and osteogenic gene expression to compare with the results for basic medium, although the results showed no statistically significant difference between the culture mediums ( Supplementary Figure 6 ). In a previous work ( Salgado et al, 2019 ) and according to the literature ( Scotti et al, 2013 ; Stüdle et al, 2018 ), the in vivo experiment was performed with 3D cultures in the presence of the osteoinductive medium. Dynamic culture conditions were chosen, as they enhanced the dental follicle MSCs migration into the inner part of the scaffold, favoring mass transfer and oxygenation, avoiding the hypoxia-necrosis effect of in vitro engineered tissues.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These scaffolds under osteoinduction medium were characterized by DNA concentration, ALP activity and osteogenic gene expression to compare with the results for basic medium, although the results showed no statistically significant difference between the culture mediums ( Supplementary Figure 6 ). In a previous work ( Salgado et al, 2019 ) and according to the literature ( Scotti et al, 2013 ; Stüdle et al, 2018 ), the in vivo experiment was performed with 3D cultures in the presence of the osteoinductive medium. Dynamic culture conditions were chosen, as they enhanced the dental follicle MSCs migration into the inner part of the scaffold, favoring mass transfer and oxygenation, avoiding the hypoxia-necrosis effect of in vitro engineered tissues.…”
Section: Resultsmentioning
confidence: 99%
“…This type of scaffolds has shown osteoconductive properties to MSCs which expressed osteoblast-like gene markers ( McCafferty et al, 2014 ). Also, recent studies showed that nanohydroxyapatite integrated in scaffolds was capable to recruit bone marrow MSCs and promote their osteogenic differentiation ( Rodrigues et al, 2013 ; Salgado et al, 2016 , 2019 ). In this work, the results illustrated the ability of dental MSCs cultured in biocomposite cryogels to differentiate into osteoblastic cells, with high ALP enzyme activity and bone phenotype gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations